-8a-b-(-6c)-2a-b-5c=0

Simple and best practice solution for -8a-b-(-6c)-2a-b-5c=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8a-b-(-6c)-2a-b-5c=0 equation:


Simplifying
-8a + -1b + -1(-6c) + -2a + -1b + -5c = 0

Remove parenthesis around (-6c)
-8a + -1b + -1 * -6c + -2a + -1b + -5c = 0

Multiply -1 * -6
-8a + -1b + 6c + -2a + -1b + -5c = 0

Reorder the terms:
-8a + -2a + -1b + -1b + 6c + -5c = 0

Combine like terms: -8a + -2a = -10a
-10a + -1b + -1b + 6c + -5c = 0

Combine like terms: -1b + -1b = -2b
-10a + -2b + 6c + -5c = 0

Combine like terms: 6c + -5c = 1c
-10a + -2b + 1c = 0

Solving
-10a + -2b + 1c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2b' to each side of the equation.
-10a + -2b + 2b + 1c = 0 + 2b

Combine like terms: -2b + 2b = 0
-10a + 0 + 1c = 0 + 2b
-10a + 1c = 0 + 2b
Remove the zero:
-10a + 1c = 2b

Add '-1c' to each side of the equation.
-10a + 1c + -1c = 2b + -1c

Combine like terms: 1c + -1c = 0
-10a + 0 = 2b + -1c
-10a = 2b + -1c

Divide each side by '-10'.
a = -0.2b + 0.1c

Simplifying
a = -0.2b + 0.1c

See similar equations:

| x-3/10-8=3x+2 | | 6-2x+7-3x=12 | | 2*6*w+2*w*8+2*6*8=208 | | 9x-7=9(x-5) | | 15/2((64)-1/2) | | -2c=pm^2-n | | -(x+2)=-18-x | | X-5/3=5/4 | | x/5=-23 | | 1/2(0.75-0.25) | | -8x+16=-3x-4 | | 3(43)-8+43+2(98.5)-17=180 | | 7d-12+3=18 | | 32-8k=-6+6(-7-8k) | | 6r^2+13r-63=0 | | 1.00/2.00(0.75-0.25) | | 8p-11=5 | | 12x+17=18x-17 | | .50x+.50(100)=.25(140) | | -3m+8-m=-6-3m | | 1.00/2.00(x-0.25) | | -20-3x-5=22x-5 | | T=L(6+RS) | | 15=K(3) | | 11=15x+16 | | u/6=11/17 | | 1/2x+5=-2 | | (9+2x)(6)=14+7x | | 8x+5=2x-4 | | (n-1/2)=17 | | 2t+10+t=-7 | | .5x-6=-1 |

Equations solver categories